Body mass index is inversely associated with capillary ketones at the time of colonoscopy: Implications for SGLT2i use. (26th October 2021) - Hamblin, Peter S.; Wong, Rosemary; Ekinci, Elif I.; Sztal‐Mazer, Shoshana; Balachandran, Shananthan; Frydman, Aviva; Hanrahan, Timothy P.; Hu, Raymond; Ket, Shara N.; Moss, Alan; Ng, Mark; Ragunathan, Sashikala; et al.
Abstract: Objective: Sodium–glucose cotransporter 2 inhibitors (SGLT2i) have been associated with diabetic ketoacidosis at the time of colonoscopy. This study aimed to identify factors associated with ketone concentrations in SGLT2i‐treated type 2 diabetes compared with non‐SGLT2i‐treated diabetes, and those with impaired fasting glycaemia (IFG) and normoglycaemia. Design: Cross‐sectional, multicentre, observational study June–December 2020 in four Australian tertiary hospitals. Participants: Capillary glucose and ketones were measured in people undergoing colonoscopy: 37 SGLT2i‐treated and 105 non‐SGLT2i‐treated type 2 diabetes, 65 IFG and 151 normoglycaemia. Measurements: Body mass index (BMI), age, glucose, fasting duration and where relevant, HbA1c and time since last SGLT2i dose. Results: In SGLT2i‐treated diabetes, BMI ( ρ  = −0.43 [95% confidence interval: −0.67, −0.11]) and duration since last SGLT2i dose ( ρ  = −0.33 [−0.60, 0.00]) correlated negatively with increasing ketones, but there was no correlation with fasting duration. In non‐SGLT2i‐treated diabetes, BMI correlated negatively ( ρ  = −0.24 [−0.42, −0.05]) and fasting duration positively ( ρ  = 0.26 [0.07, 0.43]) with ketones. In IFG participants, only fasting duration correlated with ketones ( ρ  = 0.28 [0.03, 0.49]). In normoglycaemic participants, there were negative correlations with BMI ( ρ  = −0.20 [−0.35, −0.04]) and fasting glucose ( ρ  = −0.31 [−0.45, −0.15]) and positive correlations with fasting duration ( ρ  = 0.20 [0.04, 0.35]) and age ( ρ  = 0.19 [0.03, 0.34]). Multiple regression analysis of the entire cohort showed BMI, age and fasting glucose remained independently associated with ketones, but in SGLT2i‐treated participants only BMI remained independently associated. Conclusions: In SGLT2i‐treated diabetes, lower BMI was a novel risk factor for higher ketones precolonoscopy. Pending larger confirmatory studies, extra vigilance for ketoacidosis is warranted in these people.